Synthesis, Crystal Structure and Fluorescent Property of 2-(2-(Diphenylamino)-2-oxoethoxy)-N-(pyridin-2- ylmethyl)benzamide - ZHANG, SHU-SHENG; WEN, HUI-LING; WEN, YONG-HONG; LI, XUE-MEI (Asian Journal of Chemistry, 2010)
The crystal structure of 2-(2-(diphenylamino)-2- oxoethoxy)-N-(pyridin-2-ylmethyl)benzamide has been determined by single crystal X-ray diffraction method. The crystal belongs to triclinic system, space group P-1 with unit cell constants a = 9.6256(6), b = 10.3653(7), c = 12.0927(8) Å, α = 94.7570(10), β = 91.2490(10), γ = 108.4670(10), V = 1138.97(13) Å3, Z = 2, Dc = 1.276 g/cm3, μ = 0.084 mm-1, F(000) = 460, R and wR are 0.0551 and 0.1504, respectively for 4386 unique reflections with 3137 observed reflections (I > 2σ(I)). Molecules of the compound are linked into ribbons along the b axis, via C17-H17A···O3 and C26-H26A···N1 intermolecular interactions. The packing is further stabilized by Van der Waals forces. The fluorescent property of compound was also reported.